Growth and photosynthetic response of four Malaysian indigenous tree species under different light conditions. - Kenzo, Tanaka; Yoneda, Reiji; Matsumoto, Yoosuke; Alias, Mohamad Azani; Nik Ab. Majid, Nik Muhamad (2011)
Growth and photosynthetic response of four indigenous tree seedlings, i.e. Dyera costulata, Dipterocarpus baudii, Neobalanocarpus heimii and Gonystylus affinis were studied under different light conditions in a degraded secondary forest. Maximum photosynthesis (Amax) was measured at 2 and 12 months after planting. The ratio of variable to maximum fluorescence (Fv/Fm) was determined. Leaves measured at 2 and 12 months after planting were old leaves present on the seedlings and new leaves that had expanded after planting respectively. Seedling growth was measured over four years. Changes in the growth rate and Amax with canopy openness were categorised into two groups. The growth and Amax of the first group (D. costulata and D. baudii) were maximum at 30-40% canopy openness. This group may be suitable for planting under large canopy gaps. The second group (G. affinis and N. heimii) showed maximum growth and Amax at relatively low canopy openness (less than 20%). Leaves in the second group suffered chronic photoinhibition under large gap. These species were suitable to be planted under low light conditions.